El aprendizaje cooperativo en las escuelas interculturales bilingües :estudio de Caso del CECIB “Mariscal Sucre” de la Comunidad de Santo Domingo, Cantón Cayambe, - Patiño Caizatoa, María del Carmen (2015)
This work aims to show the strategy of cooperative learning in the daily work in the classroom, analyzing how these strategies help to interrelate the action of the teacher and students with content. Cooperative learning promotes the human being in its communication and affection as it encourages personal growth, complementarity, friendship and marriage. The work was conducted as a case study, intercultural bilingual school in Canton Cayambe, which is expected to develop in students, cooperation with others looking to anchor this practice. Throughout this paper a reference to the use of group analysis as a means of learning and personal growth as both social of those who go to this school, some topics among which highlights the theoretical foundations of cooperative learning is addressed, the guidelines of the intercultural Bilingual Education, a brief analysis of the educational institution and a proposal for cooperative work for the sixth level of EGB is presented, noting the compatibility within the framework of intercultural bilingual education. It concludes with some recommendations towards implementing cooperative work strategies within the classroom that favor the construction of knowledge, and promote the shared warmth of each member of the educational community.